A Dual-Pathway Perspective on Food Choices in Adolescents: The Role of Loss of Control Over Eating - Van Malderen, Eva; Kemps, Eva; Claes, Laurence; Verbeken, Sandra; Goossens, Lien (Frontiers in Psychology, 2021)
Introduction: One in three adolescents frequently consume unhealthy snacks, which is associated with negative developmental outcomes. To date, it remains unclear how intrapersonal factors account for food choices in adolescents. Guided by the dual-pathway model, the current study aimed to: (1) examine the joint contribution of inhibitory control and attentional bias in predicting unhealthy food choices in adolescents, and (2) determine whether this mechanism is more pronounced in adolescents who experience loss of control over eating (LOC). Materials and Methods: A community sample of 80 adolescents (65% female; 10 – 17 years old, Mage = 13.28, SD = 1.94) was recruited. Based on a self-report questionnaire, 28.7% of this sample reported at least one episode of LOC over the past month. Food choice was assessed using a computerized food choice task. Both inhibitory control and attentional bias were measured with behavioral tasks (go/no-go and dot probe task, respectively). Binary logistic regressions were conducted to address the research questions. Results: Inhibitory control and attentional bias did not significantly interact to predict unhealthy food choices. However, there was a significant three-way interaction between inhibitory control, attentional bias and LOC. For adolescents without LOC, the combination of poor inhibitory control and low attentional bias was significantly associated with unhealthy food choice. Surprisingly, for adolescents with LOC, there was no significant association between unhealthy food choice and inhibitory control or attentional bias. Discussion: Dual-pathway processes do not seem to add to the explanation of food choice behavior for adolescents with LOC. For adolescents who do not experience LOC, those with poor inhibitory control combined with low attentional bias might be at particular risk for making unhealthy food choices.